Adaptation Strategies of Culinary MSMEs in Facing Rising Production Costs in Jambi City - Rizka Wahyuni; Yuliana Saputri; Dhefarell Jalingga; Ilham Muhammad Fitrah; Monic Falencia; Julaikha Rosiana Dewi; Ahmad Rifki (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Rising production costs have become a serious challenge for culinary Micro, Small, and Medium Enterprises (MSMEs) in Jambi City, particularly due to limited capital and competitive pressures that prevent business operators from raising selling prices directly. This study aims to analyze the impact of rising production costs on business operations and profitability, as well as to identify the adaptation strategies employed by culinary MSME operators in response to these conditions. The study employed a descriptive qualitative approach, collecting data through semi- structured interviews with six culinary MSME operators in Jambi City, including sellers of Sate Padang, Gado-gado, Siomay, Batagor, Es Tebu, Es Pisang Ijo, and Es Doger. Informants were selected using purposive sampling, and data validity was verified through triangulation. The findings reveal that all business operators experienced a direct impact from rising production costs, particularly in plastic packaging, primary raw materials, and supporting materials, which ultimately led to a decline in daily net income. The adaptation strategies implemented include reducing product portions without raising prices, switching to more economical packaging, sourcing alternative suppliers, and utilizing social media as a promotional tool.